Cultivo de Haematococcus pluvialis Flotow (Chlorophyceae) em sistema fototrófico e mixotrófico a base de meio alternativo - Truzzi, Bruno Scardoeli [UNESP] (2016)
Microalgae are organisms with diversified biochemical composition and are increasingly being focused by several commercial firms and research areas to obtain compounds with high commercial value. Some species, such as the microalga Haematococcus pluvialis, are cultivated on a large scale and have a fundamental role as feed sources of water organisms. Growth, development and biochemical composition of the algae are affected by several factors such as the culture medium and breeding conditions. One of the most important issues in the large scale production of these microorganisms is high production costs especially due to the formulation of culture media. Current paper evaluates the performance of microalga H. pluvialis bred in alternative culture media with low production costs when compared to WC commercial medium under phototrophic and mixotrophic culture conditions. In phototrophic conditions, the microalga was cultivated in a medium based on the inorganic fertilizer NPK at different ratios (20:5:20, 12:6:12, 10:10:10 and 4:14:8), whereas in mixotrophic conditions it was tested by adding sugar cane molasses as the organic source for carbon. Current analysis was performed in a 2-L volume in controlled conditions. The microalga Haematococcus pluvialis grew and developed successfully when cultivated in an alternative medium based on inorganic fertilizers under phototrophic conditions. In the case of mixotrophic culture with sugar cane molasses as an alternative glucose source, biomass production was directly affected by the culture medium used. The ratio 10:10:10 had high cell density when compared to that of WC commercial medium, more appropriate for high productivity. Culture medium also influenced the biochemical composition of the species with high levels of proteins and total amino acids and low production of lipids due to the high availability and intake of nitrogen and phosphorus in the culture. The addition of molasses may be an economical alternative in the substitution of organic sources of carbon commonly used in mixotrophic culture and may stimulate the growth of H. pluvialis and induce higher production of total amino acids. However, the growth of the microalga in a fertilizer-based medium was not satisfactory and revealed that the culture medium also influenced the culture conditions. When results were compared for the conditions of the tested culture, the microalga Haematococcus pluvialis developed better under phototrophic conditions. The use of culture media with alternative nutrient sources was an adequate technique to lower production costs and obtain high productivity with high nutritional rates.